Clinico-dermoscopic study of inflammatory dermatoses: a hospital based cross sectional study - Thapa, Deeptara Pathak; Pradhan, Sushmita; Adhikari, Harihar; Bhandari, Sajana; Paudel, Prabhat (Nepal Medical College Journal, 2023)
Dermoscopy is a noninvasive, fast, and reliable diagnostic technique used to magnify and visualize structures on and beneath the skin surface which is difficult to observe by naked eyes, creating a link between macroscopic clinical dermatology and microscopic dermatopathology. The purpose of this study is to evaluate and compare the dermoscopic features of common inflammatory dermatological conditions of skin sharing similar clinical presentation according to the available literature data. All dermoscopic findings were studied using a handheld pocket dermoscopy (Dermlite DL1) with high magnification. Variables used for dermoscopic evaluation were divided into vascular and nonvascular features and specific clues. Descriptive analysis and Chi square test were used where appropriate and p < 0.05 was considered statistically significant. There were a total of 205 patients enrolled in the study. The most common clinical diagnosis was psoriasis seen in 42.0%, lichen planus in 13.0%, contact dermatitis in 12.0%, polymorphic light eruption 7.0%, seborrheic dermatitis 4.0%, discoid lupus erythematosus 5.0%, pityriasia Rosea 5.0%, urticaria 5.0% and others 7.0%. Dermoscopic vascular changes were seen as regular in 52.0% and irregular in 46.0%. The most common type of vessels observed were dotted in 70.0%, linear in 7.0%, and coiled in 2.0%. Non-vascular changes were seen in 61.0%. The commonest type of scales were whitish scales seen in 63.0%. Pigmentary changes were seen in 19.0%. The commonest type of vessels observed were dotted vessels (p value 0.000) in most inflammatory diseases. Features like wickham striae were characteristic of lichen planus (p value 0.000). The characteristic dermoscopic features of various inflammatory disorders with the help of a dermoscope is easy to perform in outpatient without any invasive method and also helpful in guiding management of the patients with follow-up.